2023
DOI: 10.1371/journal.pone.0284895
|View full text |Cite
|
Sign up to set email alerts
|

Asian ageing: The relationship between the elderly population and economic growth in the Asian context

Abstract: The elderly population and economic growth have been a contentious topic among researchers. Regardless of the economic growth rate, the population and its growth have a stimulating influence on economic development. This study aims to explore the relationship between the elderly population and economic growth in 15 Asian countries, based on secondary data gathered from the WDI (World Development Indicators) from 1961 to 2021. This research contributes to filling the empirical gap, capturing the Granger causali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Each variable in a VAR model has a linear function of its prior values and the values of other variables [ 44 , 45 ]. The mathematical Eq 1 of the VAR model, initially supported by [ 46 , 47 ] represents the relationship of variables to elucidate macroeconomic and socioeconomic factors impacting migration in Sri Lanka. Where migration; GDPPCI, GDP per capita income (LKR); unemployment (rate); HE, higher education (total graduate output); EG, economic growth (real GDP growth rate); a 1 , constant term; b 11 , b 12 , b 13 and b 14 coefficients; u 1t, error term; t-1, time; j = p, lag value.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each variable in a VAR model has a linear function of its prior values and the values of other variables [ 44 , 45 ]. The mathematical Eq 1 of the VAR model, initially supported by [ 46 , 47 ] represents the relationship of variables to elucidate macroeconomic and socioeconomic factors impacting migration in Sri Lanka. Where migration; GDPPCI, GDP per capita income (LKR); unemployment (rate); HE, higher education (total graduate output); EG, economic growth (real GDP growth rate); a 1 , constant term; b 11 , b 12 , b 13 and b 14 coefficients; u 1t, error term; t-1, time; j = p, lag value.…”
Section: Methodsmentioning
confidence: 99%
“…The stationarity of all variables has been established, as confirmed by the findings in Fig 3 . The VAR model is deemed stable when all the eigenvalues of its coefficient matrix are below one, as per the formal definition [ 20 , 46 , 48 ]. The S7 and S8 Appendices revealed that the eigenvalues in the researchers’ predictors fall within the unit circle; in Fig 3 , VAR model stratifies the stability criterion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to some scholars, it is a person's subjective perception of a scarcity of pleasant human connections (Huxhold et al, 2022), meaning that feelings of loneliness may persist even while accompanied by others (Neves et al, 2019). Pakistan, like many other countries, is witnessing demographic upheavals as a result of improved healthcare and higher life expectancy (Jayawardhana et al, 2023). Therefore, this demographic transformation necessitates the identification and management of specific aging-related requirements and difficulties (Van Orden et al, 2021).…”
Section: Introductionmentioning
confidence: 99%